Avanços instrumentais e desenvolvimento de metodologia analítica para separação de monossacarídeos em microssistemas eletroforéticos com detecção condutométrica sem contato - Duarte Junior, Gerson Francisco (2015)
The current work describes some instrumental advances on contactless conductivity detection (C4D) as well as the development of ionic electrodes to be coupled on microchips electrophoresis (MSE). Firstly, was constructed a high-resolution C4D detector based on openC4D electronic. Frequency and amplitude was optimized resulting in 400 kHz and 4 Vpp, respectively, for optimal values. These conditions was able to be used in different MSE devices including polymethylmethacrylate, polydimethysiloxane and polyester-toner. For liquid electrodes fabrication, channels were engraved on a polymeric plate using a CO2 laser system and sealed with adhesive membrane. After that, PDMS microchip was reversibly sealed against the polymer membrane. The electrode channels were filled with different ionc solutions (KCl, NaCl and LiCl). The KCl solution with 2 mol/L provide the best peak intensity. Then analytical performance of the ionic electrode was test in a separation of K+, Na+ e Li+ (300 μmo/L each). A good separation was observed and limit of detection achieved were 28, 40 and 58 μmol/L for K+, Na+ e Li+, respectively. The biggest advantage the use of ionic electrode are related of easiness fabrication process, simplicity and lower cost per device. Additionally, a commercial system of MSE-C4D was propose in a separation of sugars. The analytical separation was realized under the alkaline condition (pH>12), in order to provide the negative charge for sugars. After optimization of buffer and experimental conditions, a mixture containing fructose, galactose, glucose, lactose and sucrose was separated in less 3 min.